Thermal characteristics of grinding fluids - Massam, Mark (Cranfield University, 2008)
High Efficiency Deep Grinding (HEDG) combines high depths of cut, high grinding wheel speeds with high work piece feed rates to deliver a very high stock removal process that can produce components free of surface damage. High contact temperatures are a characteristic of the process and this produces a mass of hot grinding sparks being ejected from the grinding zone. Neat oil cutting fluids are typically used in HEDG due to their excellent lubricity, but the high grinding wheel speeds employed leads to high levels of highly volatile cutting fluid mist in the machine canopy. This mist can mix with the hot grinding sparks being ejected from the grinding zone to create a potential fire hazard. The project aim was to produce a cutting fluid application strategy for the HEDG regime, focusing on establishing the thermal characteristics of cutting fluids in order to determine the optimum cutting fluid for the HEDG process. The cutting fluid application strategy also involved investigating the optimum means by which to apply the cutting fluid, based on minimising amount of cutting fluid used in the process and in reducing the potential fire hazard. The characteristics that have a thermal impact on the grinding process are the cooling, lubrication, ignition and misting properties of the fluid. A series of tests were established to investigate these properties and therefore allow different fluids to be compared and contrasted for their suitability for the HEDG regime based. Once an optimal cutting fluid had been established, the project then investigated the optimal method of applying this fluid, with particular reference to the type and design of the nozzle used to apply the fluid to the grinding zone. As part of these trials, a series of benchmark tests were also conducted using long established cutting fluid application techniques to enable the benefits of the new strategy to be evaluated. The project concluded that high viscosity neat oil ester based cutting fluids were the best fluids to be used in the HEDG regime due to they excellent lubricity and low misting properties coupled to their relatively high resistance to ignition when compared to neat mineral oils. The studies also found that using a high viscosity ester based fluid and then applying it using a coherent jet nozzle, significant reductions in the grinding powder and specific grinding energy could be achieved whilst significantly lowering the amount of mist in the machine, thus reducing the potential fire hazard and the volume of cutting fluid used by the process.
Keywords: HEDG; Fluid Application; Convection Coefficient; Misting; Fire Hazard